“Say a Little but Say It Well”: Assessing the Impact of Social Media Communication on Value Co-creation, Online Customer Experience, and Customer Well-Being - Awan, Maheen Iqbal; Shamim, Amjad; Saleem, Muhammad Shoaib (Frontiers in Psychology, 2022)
The purpose of the study is to identify how both tourism service provider- and tourist-generated social media communication affect the value co-creation process and how this can affect online customer experience and customer well-being. A questionnaire survey was used and 361 valid responses were obtained from Malaysian citizens. The research findings showed that tourism service provider- and tourist- generated social media communication positively influence value co-creation. Similarly, value co-creation positively influences cognitive and affective experiential states and these two states positively influence customer well-being. Furthermore, value co-creation partially mediates the relationship between social media communication and online customer experience, whereas, online customer experiences also partially mediate the relationship between value co-creation and customer well-being. This study has tried to establish theoretical relationship between some significant variables and the findings would aid both academicians and practitioners in formulating strategies for future.